Exploring Digital Formative Assessment Practices of EFL Teachers at a Chinese Vocational University - Song, Jingwei (Journal of Research in Vocational Education, 2025)
Digital formative assessment has garnered increasing academic attention within the realm of English-as-a-foreign-language (EFL) research. Leveraging the advancements in digital technologies and the pedagogical advantages of formative assessment, EFL teachers are enabled to adjust their instructional methods more promptly and provide more constructive feedback to enhance students’ learning outcomes. However, the manner in which teachers implement digital formative assessment practices in vocational EFL contexts remains underexplored. This study investigates how EFL teachers at a Chinese vocational university integrate digital platforms into their formative assessment practices. Utilising a qualitative case study approach, it explores teachers’ formative assessment practices across four digital platforms, including SuperStarLearn, FiF, iWrite, and iTest. The findings reveal that digital platforms demonstrate effectiveness in enhancing assessment efficiency, eliciting students’ learning evidence, and personalising instructional feedback. The challenges encountered in teachers’ practices are also reported. These insights contribute to a deeper understanding of digital formative assessment, offering implications for digital formative assessment practices in EFL classrooms and the development of technology-enhanced assessment solutions in vocational EFL contexts.